Adhesion performance of UHMWPE fiber treated with polyethylene wax grafted methyl methacrylate alone or in conjunction with silane coupling agent. Issue 11 (3rd June 2021) - Tian, Yonglong; Guo, Lamei
Abstract: To improve the interfacial adhesion between ultrahigh molecular weight polyethylene (UHMWPE) fiber and epoxy resin, the fiber were treated with polyethylene wax grafted methyl methacrylate (PEW-g-PMMA) alone or in combination with silane coupling agent. The factors affecting the interfacial bond property of fiber, e.g. grafting rate, coating temperature, concentration of silane coupling agent were studied. The single-fiber pull-out tests showed that compared with the pristine UHMWPE fiber, the pull-out strength of 9 wt% PEW-g-PMMA treated fiber had increased by 45.11%, and the pull-out strength of 9 wt% PEW-g-PMMA/12 wt% silane coupling agent treated fiber had increased by 77.97%. The pull-out strength of fiber increased with the increase of temperature and grafting rate. Infrared analysis indicated that several polar groups were introduced onto the fiber surface through coating treatment. SEM analysis showed that the surface of treated fibers became rougher. Contact angle tests manifested that the functional coating was conductive to improve the wettability of fiber. Tensile testing and XRD results showed that the processing procedure almost had no effect on the crystallinity and mechanical properties of UHMWPE fibers. Finite element analysis showed that the presence of functional coating can improve the ability of the interface to resist damage.